Media representations of COVID-19 public health policies: assessing the portrayal of essential health services in Canadian print media - Ubaka Ogbogu; Lorian Hardcastle (BMC, 2021)
Abstract Aims The study assessed how the Canadian print media represented essential healthcare services during the COVID-19 pandemic, including the controversial decision to include liquor and cannabis stores in essential services lists. Methods Mixed-method content analysis of 67 articles published in major Canadian English language newspapers between March 23 and April 1, 2020. Articles were analyzed and coded by two raters. Ratings were analyzed in SPSS. Results Few articles in the sample discussed essential healthcare services and the inclusion of liquor and cannabis stores in essential services lists. Majority of the articles that discussed both topics framed the discussion positively and consistently with current knowledge and evidence. Conclusion Canadian print media representations of essential healthcare services and associated public debate are largely descriptive and, therefore, fail to engage critically with or advance public understanding of an important health policy issue.